IMPLEMENTASI CONTENT-BASED FILTERING DENGAN TF-IDF DAN COSINE SIMILARITY UNTUK SISTEM REKOMENDASI DESTINASI WISATA DI ACEH TENGAH: IMPLEMENTATION OF CONTENT-BASED FILTERING USING TF-IDF AND COSINE SIMILARITY FOR A TOURIST DESTINATION RECOMMENDATION SYSTEM IN CENTRAL ACEH - Sara Oyadila; Dahlan Abdullah; Ar Razi (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
Central Aceh Regency possesses rich tourism potential, yet information about tourist destinations is often unstructured, making it difficult for travelers to choose locations that suit their preferences. This study aims to develop a tourism recommendation system based on Content-Based Filtering using TF-IDF and Cosine Similarity approaches. The system allows users to select up to five tourism-related attributes such as “culinary,” “picnic,” or “hiking” to receive destination recommendations with the highest similarity scores. The development process includes data collection from the Central Aceh Tourism Office, data preprocessing, term weighting using TF-IDF, and similarity calculation using cosine similarity. The implemented system successfully recommends three tourist destinations that best match user preferences. System testing using the black box method showed valid and expected results. The system achieved an accuracy rate of 85% during user testing, with a precision of 83% and recall of 81%, outperforming similar studies [14]. This study demonstrates that the Content-Based Filtering method is effective in delivering personalized and relevant tourism recommendations while supporting local tourism promotion efforts.